Biodegradation Technology of Organic and Inorganic Pollutants 2022
DOI: 10.5772/intechopen.101374
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biochar in Soil and Water Remediation: A Review

Abstract: In the last decades increased global environmental concerns to water and soils pollution. The main concerns are related to the contamination of the ecosystem, food security, and human health since many of the contaminants present in soil and water (residues of pesticides and antibiotics, genes of resistance to antibiotics, and heavy metals) are absorbed by plants and enter the food chain. Remediation of the contaminated water and soil to ensure sustainable water supply and food production is urgently needed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Previous studies reported that the biochar properties are highly dependent on the temperature (300-1000 • C), time of pyrolysis, final acidity, and feedstock from which the biochar is produced [27]. Compared to raw slurry, the addition of biochar to the slurry increases the pH value, C/N ratio, cation-exchange capacity, and microbial activities [28][29][30][31][32], in line with this study in which an increase in DM and NH 4 + was observed in treatments with biochar. Although the specific surface area and porosity were higher in Cardoon than Agroforestry or Elderberry, an absence of differences in the composition of treatments with biochar added to slurry was observed, which could be related to the solution pH in these treatments being similar (Table 2).…”
Section: Composition Of the Slurriesmentioning
confidence: 99%
“…Previous studies reported that the biochar properties are highly dependent on the temperature (300-1000 • C), time of pyrolysis, final acidity, and feedstock from which the biochar is produced [27]. Compared to raw slurry, the addition of biochar to the slurry increases the pH value, C/N ratio, cation-exchange capacity, and microbial activities [28][29][30][31][32], in line with this study in which an increase in DM and NH 4 + was observed in treatments with biochar. Although the specific surface area and porosity were higher in Cardoon than Agroforestry or Elderberry, an absence of differences in the composition of treatments with biochar added to slurry was observed, which could be related to the solution pH in these treatments being similar (Table 2).…”
Section: Composition Of the Slurriesmentioning
confidence: 99%
“…In recent years, biochar has been widely investigated as a nutrient carrier with slow-release capacity, an additive reducing soil water loss, or sorbent of various xenobiotics [ 1 , 2 , 3 ]. The most important properties of biochar determining its high adsorptive potential are: large surface area, porous structure, abundance in surface functional groups, and high cation exchange capacity [ 4 ]. These features may induce chemical immobilization of contaminant molecules on biochar and as a result mitigate their leaching and bioavailability.…”
Section: Introductionmentioning
confidence: 99%